Оцінка міцності і придатності для використання з’єднань з натягом з геометричними аномаліями - Андрєєв, Арнольд Георгійович; Щепкін, Олександр Віталійович (НТУ "ХПІ", 2017)
Предметом дослідження є порівняльний аналіз з’єднань з натягом, які мають відхилення від правильної геометричної форми. Розглядаються різні геометричні аномалії форми валу: конічна, бочкоподібна, сідлоподібна, посадка валу еліптичної форми в круглу втулку. Результати наводяться у формі таблиць і рисунків. Виконані дослідження дозволяють дослідити вплив параметрів з'єднання на його міцність, намітити раціональні шляхи його зміцнення.

In machinery and manufacturing equipment the process of details connection by heavy-shrink fitting is widely applied. Such type of connection allows to transfer heavy axial forces and twisting moments. Connection durability in the heavy-shrink fitting is due to elastic, and sometimes also plastic deformation, which arise at technological process of assembly. Connection durability depend from relative size of a tightness, material characteristics, quality of surfaces, assembly procedure. Connection durability depend also from geometrical form abnormalities of connecting details. The work carry out the analysis of deflected mode of heavy-shrink fitted bush and shaft. We consider all possible options such as planting: tapered shaft, barrel shaft, saddle shaft, elliptical shaft to bush with round hole. The results are summarized in the form of tables and figures. The executed researches allow to trace influence of parameters of connection on his durability, to plan the rational approach of his work-hardening.
Estimation of durability and fitness for use of connections with a heavy-shrink fitting with geometrical abnormalities
Keywords: втулка; вал; посадка з натягом; метод скінченних елементів; bush; shaft; heavy-shrink fitting; finite element method